A metal–organic framework based on cyclotriphosphazene-functionalized hexacarboxylate for selective adsorption of CO2 and C2H6 over CH4 at room temperature1. Issue 33 (7th September 2015) - Ling, Yajing; Song, Chengling; Feng, Yunlong; Zhang, Mingxing; He, Yabing
<x xml:space="preserve">Abstract</x> A new MOF constructed from a flexible cyclotriphosphazene-functionalized hexacarboxylate exhibits selective adsorption of CO2 and C2H6 over CH4 at room temperature.